Visible light communication system using mobile phone camera receiver and imaging receiver - Deng, Lingzhe (2016)
Nowadays, white light-emitting diodes (LEDs) are promising for future indoor lighting due to their advantages such as low power consumption, long lifetime, small size and cool operation. Intensity modulation with direct detection of LED as well as unlicensed visible light spectrum provide the potential of low-cost and high-speed indoor wireless visible light communication (VLC). This report describes an experimental demonstration of the indoor wireless VLC system using white LED as transmitter. An indoor wireless VLC system using white LED as transmitter and using mobile phone camera as receiver is designed and built due to the popularity of mobile devices equipped with embedded cameras. A photo containing an oversampled OOK signal is captured by CMOS sensors embedded in mobile phone camera with rolling shutter mechanism. Through experiments, 11 bits can be extracted correctly from a photo. The system data rate is found to be limited by the intrinsic property of rolling shutter effect. An indoor wireless 2 × 2 MIMO OFDM VLC system using white LEDs as transmitters and using imaging receiver is designed and built. An imaging receiver can form a well-conditioned channel matrix for MIMO signal detection and thus the system data rate can grow multiply according to the MIMO size. The OFDM signals is transmitted over a free-space distance. The raw data rate per channel is 200 Mbps using 16QAM mapping and 50 MHz modulation bandwidth, and the system data rate achieved is 400 Mbps (200 × 2 Mbps). When the distance is 1.05m and receiver position offset is 0 cm, the average BER about 3.8 × 10-3 is achieved. When the distance is 1 m and receiver position offset is 12 cm, the average BER about 3.8 × 10-3 is achieved.